Современные подходы к организации и реализации технических систем и технологий алмазно-искрового шлифования - Гуцаленко, Юрий Григорьевич; Янку, К. Г. (Лира, 2015)
Perspective directions for an applied use of the technological method of diamond-spark grinding that are being associated with the working-out of new and modernization of existing machines and tools including with the diamond abrasives of an enhanced initial integrity, high-speed processing, final shaping of high-quality ceramics after spark plasma sintering and formation of hard white layers in steels are presented.
Keywords: обработка механическая; резание; ток электрический; формообразование; скорость; слой белый; обработка термофрикционная; алмазы ультрадисперсные; синтез детонационный